2021
DOI: 10.1161/circinterventions.120.010308
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of the Coarctation of the Aorta Stent Trials

Abstract: Background: Long-term outcome data of stent-implantation for coarctation of the aorta are limited. We report up to 5 years of postimplant follow-up in patients enrolled into the COAST (Coarctation of the Aorta Stent Trial) and the COAST II trial (Covered Cheatham-Platinum Stents for Prevention or Treatment of Aortic Wall Injury Associated With Coarctation of the Aorta), evaluating the bare and Covered Cheatham-Platinum Stents for the treatment of coarctation of the aorta and associated aortic wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 13 publications
1
39
2
Order By: Relevance
“…In the future, long-term assessment will become increasingly more important in CHD since the quality of treatment frequently does not become apparent within the first months after the procedure. 20,21 Combined case group analysis provides a real, live description of the time and effort and the performance of surgical and interventional treatment in Germany. 22 Cases planned with single interventions required the least Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, long-term assessment will become increasingly more important in CHD since the quality of treatment frequently does not become apparent within the first months after the procedure. 20,21 Combined case group analysis provides a real, live description of the time and effort and the performance of surgical and interventional treatment in Germany. 22 Cases planned with single interventions required the least Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, long-term assessment will become increasingly more important in CHD since the quality of treatment frequently does not become apparent within the first months after the procedure. 20 21 …”
Section: Discussionmentioning
confidence: 99%
“…139 The intermediate results of 1 study demonstrated that 4% of patients with stenting of the CoA underwent an unplanned reintervention because of recurrent coarctation or pseudoaneurysm formation, with an average time to reintervention of 2.84 years, whereas another study found a cumulative aneurysm incidence of 6% at 5 years. 9,139 The availability of covered stents (balloon-expandable or self-expanding) platforms may further improve the safety profile of stents, reduce catastrophic aortic wall injury, and allow the treatment of CoA-associated pseudoaneurysms or aneurysms.…”
Section: Aortic Interventionsmentioning
confidence: 99%
“…For example, patients with cyanosis, low muscle mass, or hepatic congestion due to rightheart disease or Fontan circulation have more renal and hepatic dysfunction than is apparent using standard laboratory evaluation and have a higher risk of bleeding. is a powerful quality improvement tool for pediatric and adult congenital cardiac catheterizations 8 ; the other multicenter collaborations include the Congenital Cardiac Interventional Study Consortium 9 and Congenital Cardiac Catheterization Project on Outcomes. 10 Patient heterogeneity, variability in procedural selection and techniques, the need for extensive and detailed data entry, and rapid changes in available technologies have long been a significant challenge in registry and outcome research in ACHD; however, this has been somewhat mitigated by the electronic medical records and increased resources available for quality improvement and research.…”
Section: Introductionmentioning
confidence: 99%
“…Early results of the BeGraft aortic stent in the pediatric population, which has the advantage of large postdilation diameter up to 3 cm and low profile, have been very good, although more data is needed on medium-term to long-term outcomes [44][45][46]. There have also been studies confirming medium-term to long-term outcomes in young infants requiring balloon angioplasty [22] and coarctation patients treated with covered stents [47,48]. In spite of promising outcomes of percutaneous strategies, many studies continued to show a risk for reintervention and arterial hypertension requiring treatment.…”
Section: Percutaneous Interventionsmentioning
confidence: 99%